Enterpreneurship Training of Oyster Mushroom-Based Nugget in Lembaga Pemasyarakatan Terbuka Kelas IIB Jakarta - Rianita Pramitasari; Thia Margaretha Tarigan; Rakhdiny Sustaningrum (MITRA: Jurnal Pemberdayaan Masyarakat, 2018)
Lembaga Pemasyarakatan (Lapas) Terbuka Kelas IIB Jakarta manages oyster mushroom as the potential food resource. The mushroom is cultivated by prisoners in the prison. However, it has not been utilized optimally as an effective business opportunity. The purpose of this community service was threefold, namely i) to utilize the potential of oyster mushroom in Lapas Terbuka Kelas IIB Jakarta to be processed into nugget as the food product with higher selling value; ii) to encourage prisoners’ entrepreneurship spirit; and iii) to produce oyster mushroom-based nugget continuously to increase prison productivity. The method used in this program was training the prisoners oyster mushroom-based nugget processing and packaging using vacuum packaging technology, entrepreneurship and marketing strategy, as well as financial accounting. Afterwards, nugget processing, packaging, and simple financial accounting practice were conducted. The evaluation was conducted after two months of training to evaluate the implementation of nugget entrepreneurial activities in prison. The program was attended by prisoners and prison staff members. Through this community service program, we hope oyster mushroom cultivation in prison could be utilized more effectively so that productivity can be raised. Continuous coaching is needed to keep the production, marketing, and financial record activities work better.